1992
DOI: 10.1002/ppp.3430030313
|View full text |Cite
|
Sign up to set email alerts
|

Perennial névés and the hydrology of rock glaciers

Abstract: From 1986 to 1990 water tracing was carried out in three rock glaciers in the Upper Val de Réchy. Results indicate different patterns of circulation depending on the size and degree of activity of the rock glaciers. Two rock glaciers show rapid superficial flow and one has slow interstitial flow. This is analogous to supra‐ and subglacial flow. Intra‐flow is also seen in one rock glacier. The importance of perennial névés at the roots of rock glaciers is demonstrated. Meltwater supplies the risings and, by ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
31
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 2 publications
8
31
0
Order By: Relevance
“…Until now, most frozen soil experiments have been conducted in Scandinavia or the arctic regions, which are characterized by a different soil and snow cover type, climate and topography (Chacho and Bredthauer, 1983;Woo et al, 1982). Alpine hydrological research has predominantly been focused on snow, glacier and permafrost hydrology (Glen, 1982;Thenthorey, 1992;Singh and Singh, 2001). There is an evident and quite surprising lack of studies, as well as tools, related to small-and large-scale effects of seasonal soil frost on Alpine hydrology.…”
Section: Introductionmentioning
confidence: 98%
“…Until now, most frozen soil experiments have been conducted in Scandinavia or the arctic regions, which are characterized by a different soil and snow cover type, climate and topography (Chacho and Bredthauer, 1983;Woo et al, 1982). Alpine hydrological research has predominantly been focused on snow, glacier and permafrost hydrology (Glen, 1982;Thenthorey, 1992;Singh and Singh, 2001). There is an evident and quite surprising lack of studies, as well as tools, related to small-and large-scale effects of seasonal soil frost on Alpine hydrology.…”
Section: Introductionmentioning
confidence: 98%
“…Due to the presence of boulder material, surface runoff from rock glaciers is almost non-existent, as the water drains underground within the landform (Corte, 1976), and especially at the permafrost table (a few meters below the surface). Tenthorey (1992Tenthorey ( , 1994 summarized the functioning of the internal drainage system of rock glaciers under three types of transfers. The first is rapid and superficial, and occurs above the permafrost layer when the daily mean air temperature is above zero.…”
Section: Introductionmentioning
confidence: 99%
“…Base flow was reported to be relatively minor in these systems and these flow rates were not quantified. Another study of groundwater flow through rock glaciers also employed a tracer test on three rock glaciers in the Alps [ Tenthorey , ]. This study suggested fast “supraflow” velocities of 0.058 m s −1 and “intraflow” velocities of 0.0002–0.0004 m s −1 .…”
Section: Introductionmentioning
confidence: 99%